Asymmetric synthesis of isoquinolinonaphthyridines catalyzed by a chiral Brønsted acid. Issue 31 (24th July 2017) - Li, Jianjun; Fu, Yiwei; Qin, Cong; Yu, Yang; Li, Hao; Wang, Wei
Abstract : A mild and efficient asymmetric cyclization reaction catalyzed by chiral Brønsted acids has been developed for the synthesis of chiral isoquinolinonaphthyridines. Abstract : A catalytic asymmetric method for the synthesis of chiral isoquinolinonaphthyridines has been developed. A chiral disulfonimide catalyzes a redox cyclization reaction between 2-methyl-3-aldehydeazaarenes and 1, 2, 3, 4-tetrahydroisoquinolines to deliver a range of isoquinolinonaphthyridines with good to high yields (up to 91%) and up to 92 : 8 er.